2023
DOI: 10.20463/pan.2023.0004
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of voluntary gait adaptability tasks requiring cognitive demands in older adults

Abstract: [Purpose] Voluntary gait adaptability is a complex construct that requires cognitive demands and dynamic balance control; it also has implications for the daily lives of older adults. This ability has been extensively studied, however, a comprehensive overview of appropriate tasks for measuring voluntary gait adaptability in older adults is lacking. Our scoping review aimed to identify existing voluntary gait adaptability tasks for older adults, summarize the specific methodological features requiring cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…All these studies used a wide variety of experimental setups, protocols and training durations making it difficult to compare results across studies and draw conclusions about the timescale at which adaptations take place, as a recent scoping review also found for gait adaptability tasks (Kim et al 2023). As a result, further research is needed to fully understand the most effective and generalisable components of proactive gait adaptability training for falls prevention.…”
Section: Training Proactive Gait Adaptationmentioning
confidence: 99%
“…All these studies used a wide variety of experimental setups, protocols and training durations making it difficult to compare results across studies and draw conclusions about the timescale at which adaptations take place, as a recent scoping review also found for gait adaptability tasks (Kim et al 2023). As a result, further research is needed to fully understand the most effective and generalisable components of proactive gait adaptability training for falls prevention.…”
Section: Training Proactive Gait Adaptationmentioning
confidence: 99%